The effectiveness of a digital shared decision-making tool in hormonal contraception during clinical assessment: study protocol of a randomized controlled trial in Spain - Maria Inmaculada de Molina-Férnandez; Laia Raigal-Aran; Miriam de la Flor-Lopez; Paula Prata; Isabel Font-Jimenez; Francesc Valls-Fonayet; Gemma March-Jardi; Ramon Escuriet-Peiro; Lourdes Rubio-Rico (BMC, 2019)
Abstract Background Decision-making tools represent a paradigm shift in the relationship between the clinician and the user/patient. Some of their advantages include patient commitment, the promotion of preferences and values, and increased treatment adherence. This study protocol aims to assess the effectiveness of a decision-making tool in contraception (SHARECONTRACEPT) concerning: a) Improvement in counselling on hormonal contraception at the medical consultation, measured in terms of decreasing decisional conflict and improving knowledge of available contraceptive options; b) Improvement in adherence to treatment measured in terms of: persistence in the chosen treatment, compliance with dose or procedure of use, and ability to deal with incidents related to the use of the contraceptive method; and decreasing unwanted pregnancies and voluntary interruption of pregnancy. The SHARECONTRACEPT tool, developed by previous phases of this project, is available at: http://decisionscompartides.gencat.cat/en/decidir-sobre/anticoncepcio_hormonal/ Methods/design A longitudinal, prospective-type, randomized, controlled community clinical trial, carried out in the clinical contraceptive counselling units of 6 autonomous regions in Spain, with an experimental group and a control group. Description of the intervention: The health professionals participating will be randomly assigned to one of the two groups. Clinicians assigned to the experimental group will perform contraceptive counselling assisted by SHARECONTRACEPT, and those of the control group will follow the conventional contraceptive counselling provided in their clinical unit. It is planned to study 1708 users (control group n = 854 and intervention group n = 854), recruited from women who attend the consultations of the health professionals. The selected users will be followed up for one year. The data will be collected through ad-hoc questionnaires, and validated instruments for measuring decisional conflict and adherence to treatment. Discussion The results of this study protocol will offer evidence of the effectiveness of a shared decision-making tool, SHARECONTRACEPT, which may prove a useful tool for users and professionals to promote adherence to contraceptive methods. Trial registration Clinical Register number ISRCTN5827994. Date: 15/04/2019 (Retrospectively registered)